Sulphide based anode material for lithium rechargeable battery - Mohamed, N.S.; Arof, Abdul Kariem; Sanusi, A.; Yahya, M.Z.A.; Navaratnam, S.; Basirun, Wan Jefrey; Alias, Y. (Springer Verlag (Germany), 2003)
In this study, lead sulphide (PbS) was prepared by the chemical bath deposition technique. The sample was characterized by X-ray diffraction (XRD), Energy Dispersive Analysis of X-rays (EDAX) and cyclic voltammetry. EDAX spectrum shows peaks attributable to lead and sulphur. The EDAX analysis also shows that the prepared sample is stoichiometric. Cyclic voltammetry experiments were recorded at 100 mV-s-1 and 400 mV-s-1 scan rates. Results show that the rate controlling electrochemical reaction is electron transfer. The presence of redox waves shows that the lithium intercalation and deintercalation can occur as a result of lattice expansion in PbS. There were no differences in the PbS XRD data before and after the cyclic voltammetry experiments indicating that the PbS structure is not modified upon lithium ion intercalation and deintercalation in PbS. The discharge characteristics for 35 cycles of the cell using the LiCoO2/PbS couple is presented indicating the possible development of such materials as anode in lithium ion cells.